Selling (un)real estate with "Shi(势)-nema": manipulation, not persuasion, in China's contemporary cinematic-cities. Issue 1 (1st January 2020) - Fleming, David H.; Harrison, Simon
ABSTRACT: Investigating what has been called the mise-en-scene of Capitalism's Second Coming in China, this essay explores how cinematic principles have become divorced from the medium of cinema and can be found operating within contemporary Chinese urban spaces in order to increase the efficacy of real estate showroom settings. Specifically, we explore the effects of affectively distributed networks of human, architectural and nonhuman "actors" that appear to be arranged in such a way as to manipulate and impact the thoughts, feelings and actions of potential buyers. To best expose the effectiveness of these modern urban assemblages, we engineer an encounter between the Chinese concept of shi (势) – described by sinologist-philosopher François Julien as the "inherent potentiality at work in configuration" – and that of cinematicty, wherein the cinema and city are recognised as co-determining and mutually enabling site/sights.